Intra-strain Differences in Young Rats Fed on Cafeteria Diet as Determined by Calorimeter and Comparative Carcass Techniques - Mohd Nor, Ismail (1985)
The effects of cafeteria feeding on body composition, metabolizable energy (ME) intake and energy expenditure of young Sprague Dawley rats obtained from two different colonies (SDQEC and SDCR) were studied. The ME intake increased significantly (P < 0.01) from 21% in SDQEC to 31% in SDCR cafeteria fed rats, with a significant change (P < 0.05) in body weight and body fat in the latter but not the former. This mild hyperphagia induced a significant increase (P < 0.01) in energy expenditure in cafeteria fed rats as compared to their respective controls. These results confirm the presence of intra-strain variations and reaffirm the validity of the carcass comparative technique for estimating energy expenditure in rats.